An example of a knotted high molecular weight (HMW) glutenin (from a gluten simulation with ρ = 4 nm −3 ). - Łukasz Mioduszewski (8967434); Marek Cieplak (257613) (2021)
Knotted area is shown in red, knot ends are indicated by black arrows. (TIF)